2017
DOI: 10.1039/c7sm02141k
|View full text |Cite
|
Sign up to set email alerts
|

A novel thermo-responsive supramolecular organogel based on dual acylhydrazone: fluorescent detection for Al3+ ions

Abstract: A new dual acylhydrazone-functionalized gelator (L) has been synthesized, which behaves as a thermal-responsive supramolecular organogel (L-gel) in DMSO. This L-gel exhibits very weak fluorescence based on the photoinduced electron transfer (PET) mechanism. The L-gel can recognize Al and assemble into an enhanced blue-light-emitting supramolecular metallogel (Al@gel).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(22 citation statements)
references
References 66 publications
0
22
0
Order By: Relevance
“…Typically, low molecular weight organogelators form networks through physical interactions, while polymeric organogelators form networks through chain entanglements or a combination of chemical and physical cross-linking . Organogels can be responsive to a number of external stimuli depending on the cross-linking chemistry, including light, , temperature, ,, redox agents, ,, and ultrasound . Light is a useful external trigger to induce responses in stimuli-responsive materials, as it can be applied locally without suffering from diffusion effects and be switched “on” and “off” easily .…”
mentioning
confidence: 99%
“…Typically, low molecular weight organogelators form networks through physical interactions, while polymeric organogelators form networks through chain entanglements or a combination of chemical and physical cross-linking . Organogels can be responsive to a number of external stimuli depending on the cross-linking chemistry, including light, , temperature, ,, redox agents, ,, and ultrasound . Light is a useful external trigger to induce responses in stimuli-responsive materials, as it can be applied locally without suffering from diffusion effects and be switched “on” and “off” easily .…”
mentioning
confidence: 99%
“…Ma et al obtained a Y 3+ enhanced blue light–emitting gel with an arylhydrazone‐functionalized dual benzimidazole derivative gelator (Figure , compound 20) in a N , N ′‐dimethylformamide (DMF)–water solution. They also found that Al 3+ ions can induce a blue light–emitting metallogel with a dual arylhydrazone‐functionalized gelator (Figure , compound 21) in dimethyl sulfoxide (DMSO) . Recently, a series of luminescent metallogels were synthesized from dinuclear platinum(II) bzimpy complexes ( Figure a) by Yam and co‐workers .…”
Section: Fundamental Applications Of Metallogelsmentioning
confidence: 99%
“…19,327,332,333 Furthermore, in some cases, a heat-cool operation was performed after addition of the guest analytes onto the gels. 326,[334][335][336][337][338][339][340] Here, we discuss the possibilities of modifying gel properties by various chemical analytes in a post-assembly pathway at room temperature. Yao et al explored an acylhydrazone functionalized benzimidazole gelator in multianalyte sensing in a gel-to-gel fashion (Fig.…”
Section: (Vii) Post Assembly Fabrication Of Gels By Chemical Analytesmentioning
confidence: 99%